2018
DOI: 10.20944/preprints201801.0028.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Development and Characterization of Cross-Linked Poly(acrylic acid) Hydrogel Containing Drug by Radiation-Based Techniques

Abstract: Poly(acrylic acid) (PAAc) hydrogels possess good bioadhesive properties and allow 15 enhanced penetration of drugs. In addition, it is possible to localize the absorption site of the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…These results show that the thermal stability of the compound slightly decreases with the AAc inclusion, leaving a more significant residual mass at high temperatures. Jeong et al [ 30 ] obtained similar results using poly AAc hydrogels, which contain different metronidazole concentrations. According to the obtained thermograms, three main steps of thermal decomposition are shown: the first one is related to the evaporation of adsorbed water (weight loss about 0.2–2.7%); the second could be attributed to the destruction of poly AAc lateral groups, leading to decarboxylation or anhydride formation (weight loss of ~2.6–11.9% between 200 °C and 300 °C); and the third step is associated to main chain scission and composite depolymerization above 300 °C.…”
Section: Resultsmentioning
confidence: 75%
“…These results show that the thermal stability of the compound slightly decreases with the AAc inclusion, leaving a more significant residual mass at high temperatures. Jeong et al [ 30 ] obtained similar results using poly AAc hydrogels, which contain different metronidazole concentrations. According to the obtained thermograms, three main steps of thermal decomposition are shown: the first one is related to the evaporation of adsorbed water (weight loss about 0.2–2.7%); the second could be attributed to the destruction of poly AAc lateral groups, leading to decarboxylation or anhydride formation (weight loss of ~2.6–11.9% between 200 °C and 300 °C); and the third step is associated to main chain scission and composite depolymerization above 300 °C.…”
Section: Resultsmentioning
confidence: 75%
“…In addition, water in the polymer solution played a crucial role in realizing maximum crosslinking, resulting in a higher number of free radicals, thereby improving the generation of macroradicals. Furthermore, H atoms and –OH radicals can produce additional macroradicals by eliminating H from PVA molecules (Jeon et al 2018 ). During irradiation, radical crosslinking and chain scission are two main reactions that simultaneously occur.…”
Section: Resultsmentioning
confidence: 99%
“…This observation is consistent with literature reports indicating 37,38 that the immediate crosslinking of layers in TF designs achieves thinner and more distinct PAA layers compared to IDN designs. Additionally, it was also observed that the surfaces of the PAA top layers for TF designs were brittle and fragmented after exposure to both acidic and basic environments (Figure 3), suggesting the presence of a free PAA network at the surface since the pure PAA hydrogel is well known to have poor mechanical properties, 39 especially in a basic environment. 40,41 In contrast, the PVA network combined with PAA in the interfacial layer enabled the IDN design to maintain structural and morphological stability during the changes in pH.…”
Section: Resultsmentioning
confidence: 99%